Zoanthid mucus as new source of useful biologically active proteins. (1st March 2018) - Guarnieri, Míriam Camargo; de Albuquerque Modesto, Jeanne Claíne; Pérez, Carlos Daniel; Ottaiano, Tatiana Fontes; Ferreira, Rodrigo da Silva; Batista, Fabrício Pereira; de Brito, Marlon Vilela; Campos, Ikaro Henrique Mendes Pinto; Oliva, Maria Luiza Vilela
Abstract: Palythoa caribaeorum is a very common colonial zoanthid in the coastal reefs of Brazil. It is known for its massive production of mucus, which is traditionally used in folk medicine by fishermen in northeastern Brazil. This study identified biologically active compounds in P. caribaerum mucus. Crude mucus was collected during low tides by the manual scraping of colonies; samples were maintained in an ice bath, homogenized, and centrifuged at 16, 000  g for 1 h at 4 °C; the supernatant (mucus) was kept at −80 °C until use. The enzymatic (proteolytic and phospholipase A2 ), inhibitory (metallo, cysteine and serine proteases), and hemagglutinating (human erythrocyte) activities were determined. The results showed high levels of cysteine and metallo proteases, intermediate levels of phosholipase A2, low levels of trypsin, and no elastase and chymotrypsin like activities. The mucus showed potent inhibitory activity on snake venom metalloproteases and cysteine proteinase papain. In addition, it showed agglutinating activity towards O +, B +, and A + erythrocyte types. The hemostatic results showed that the mucus prolongs the aPTT and PT, and strongly inhibited platelet aggregation induced by arachidonic acid, collagen, epinephrine, ADP, and thrombin. The antimicrobial activity was tested on 15 strains of bacteria and fungi through the radial diffusion assay in agar, and no activity was observed. Compounds in P. caribaeorum mucus were analyzed for the first time in this study, and our results show potential pharmacological activities in these compounds, which are relevant for use in physiopathological investigations. However, the demonstration of these activities indicates caution in the use of crude mucus in folk medicine. Furthermore, the present or absent activities identified in this mucus suggest that the studied P. caribaeorum colonies were in thermal stress conditions at the time of sample collection; these conditions may precede the bleaching process in zoanthids. Hence, the use of mucus as an indicator of this process should be evaluated in the future. Highlights: The mucus of P. caribaeorum is a potential source of proteolytic enzymes, lectins, and inhibitors that act on hemostasis. Inhibition of hemorrhagic metalloproteases by P. caribaeorum mucus opens a possibility of its use in snakebite treatment. The activities detected in the mucus of P. caribaeorum indicate caution in the use of crude mucus in folk medicine. The use of P. caribaeorum mucus as an indicator of the bleaching process should be evaluated.